2019
DOI: 10.1371/journal.pgen.1008445
|View full text |Cite
|
Sign up to set email alerts
|

A novel system of bacterial cell division arrest implicated in horizontal transmission of an integrative and conjugative element

Abstract: Integrative and conjugative elements (ICEs) are widespread mobile DNA elements in the prokaryotic world. ICEs are usually retained within the bacterial chromosome, but can be excised and transferred from a donor to a new recipient cell, even of another species. Horizontal transmission of ICEclc, a prevalent ICE in proteobacteria, only occurs from developed specialized transfer competent (tc) cells in the donor population. tc cells become entirely dedicated to the ICE transmission at the cost of cell proliferat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 51 publications
0
15
0
Order By: Relevance
“…Stochastic modelling suggested that the feedback loop maintains positive output during a longer time period than in its absence (although it will drop to zero at infinite time). Previous experimental data suggested that the tc cells indeed do not return to a silent ICE clc state, but become irreparably damaged, arrest their division ( Takano et al, 2019 ) and wither ( Reinhard et al, 2013 ). However, because their number is proportionally low, there is no fitness cost on the population carrying the ICE ( Delavat et al, 2016 ; Gaillard et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stochastic modelling suggested that the feedback loop maintains positive output during a longer time period than in its absence (although it will drop to zero at infinite time). Previous experimental data suggested that the tc cells indeed do not return to a silent ICE clc state, but become irreparably damaged, arrest their division ( Takano et al, 2019 ) and wither ( Reinhard et al, 2013 ). However, because their number is proportionally low, there is no fitness cost on the population carrying the ICE ( Delavat et al, 2016 ; Gaillard et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…ICE clc transfer competence comprises a differentiated stable state, because initiated tc cells do not transform back to the ICE-quiescent state. Although tc cells divide a few times, their division is compromised by the ICE and eventually arrests completely ( Takano et al, 2019 ; Reinhard et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, infection by a phage that is not restricted by ICEVchInd5 stimulated higher frequency conjugation, while infection by a restricted phage did not. There is an expected energetic cost and accompanying growth delay associated with the formation of the conjugative machinery, as has been shown for other ICEs (52). When infected by a restricted phage, there may be little benefit for SXT ICEs to trigger conjugation, as their host cell may suffer a selective disadvantage limiting the SXT ICE's vertical transmission.…”
Section: Discussionmentioning
confidence: 99%
“…ICEclc transfer competence comprises a differentiated stable state, because initiated tc cells do not transform back to the ICE-quiescent state. Although tc cells divide a few times, their division is compromised by the ICE and eventually arrests completely 13,14 .…”
Section: Introductionmentioning
confidence: 99%